Constipation in Elderly Population and Its Appropriate Management - Alvin Hartanto Kurniawan; Ulfa Kholili; Novira Widajanti (The Indonesian Society for Digestive Endoscopy, 2020)
Constipation is a gastrointestinal disorder commonly found in the community, especially in the elderly with various comorbidities. This problem culminates with the increasing incidence along with aging, increasing therapeutic cost, and decreasing the quality of life in this population. Some of the underlying causes are the difference in the terminology of constipation, shallow understanding of its pathophysiology, and poor management. The pathophysiology, including slow transit constipation, dyssynergic defecation, and normal transit constipation, is the most critical foundation in managing constipation accordingly. Diagnostic approaches should be made by history taking, including complaints based on Rome III, lifestyle, contributing factors, past medical history, and medications. Physical examination is considered incomplete without rectal examination. Thorough history taking and comprehensive physical examination have more diagnostic value than additional physiological workup. Management of constipation consists of non-pharmacological and pharmacological approaches, such as conventional laxative or more recent agents with better efficacy. Therapeutical management should correspond to the underlying pathophysiology. Therefore it is important to be able to recognize constipation and make the right management approach in the elderly.